Tuberculosis in pediatric patients treated with anti-TNFα drugs: a cohort study. Issue 1 (December 2015) - Calzada-Hernández, Joan; Anton-López, Jordi; Bou-Torrent, Rosa; Iglesias-Jiménez, Estíbaliz; Ricart-Campos, Sílvia; Martín de Carpi, Javier; Torrente-Segarra, Vicenç; Sánchez-Manubens, Judith; Giménez-Roca, Clara; Rozas-Quesada, Librada; Juncosa-Morros, Maria; Fortuny, Clàudia; et al.
Abstract Background Adult patients receiving anti-TNFα drugs are at increased risk of tuberculosis (TB), but studies in pediatric populations are limited, and the best strategy for latent tuberculosis infection (LTBI) screening in this population remains controversial. We describe the prevalence of LTBI prior to anti-TNFα therapy and the long-term follow-up after biological treatment initiation in a cohort of children and adolescents. Methods Cohort observational study in children and adolescents receiving anti-TNFα agents in a tertiary-care pediatric hospital. LTBI was ruled out prior to the implementation of anti-TNFα drugs by tuberculin skin test (TST), and, from March 2012 on, QuantiFERON Gold-In Tube® test (QTF-G). During anti-TNFα treatment, patients were evaluated every 6 months for TB with history and physical examination. TST/QTF-G were not repeated unless signs or symptoms consistent with TB arose or there was proven TB contact. Results The final cohort consisted of 221 patients (56.1 % female; 261 treatments), of whom 51.7 %/30.0 %/17.3 % were treated with etanercept/adalimumab/infliximab, respectively, for a variety of rheumatic diseases (75.6 %), inflammatory bowel disease (20.8 %), and inflammatory eye diseases (3.6 %). The median (IQR) age at diagnosis of the primary condition was 6.8 years (2.7–11.0) and the duration of the disease before implementing the anti-TNFα agent was 1.8 years (0.6–4.2). LTBI was diagnosed in 3 adolescent girls (prevalence rate: 1.4 %; 95 % CI: 0.4–4.2) affected with juvenile idiopathic arthritis: TST tested positive in only 1, while QTF-G was positive in all cases (including 2 patients already on etanercept). They all received antiTB chemoprophylaxis and were later (re)treated with etanercept for 24–29 months, without incidences. No incident cases of TB disease were observed during the follow-up period under anti-TNFα treatment of 641 patients-year, with a median (IQR) time per patient of 2.3 years (1.4–4.3). Conclusions In our study, the prevalence of LTBI (1.4 %) was similar to that reported in population screening studies in Spain; no incident cases of TB disease were observed. In low-burden TB settings, initial screening for TB in children prior to anti-TNFα treatment should include both TST and an IGRA test, but systematic repetition of LTBI immunodiagnostic tests seems unnecessary in the absence of symptoms or known TB contact.